A recursive method for the determination of the output power spectrum of some nonlinear systems - GABOR, Andrzej; ZARZYCKI, Jan (Archives of Acoustics, 1981)
This paper presents a new method for the determination of the output power spectral density of different types of cascading a linear system with memory and a nonlinear system without memory, with a stationary Gaussian input. This method permits uniform determination of the output spectrum for each type of the systems mentioned above. The recursive form of the resulting expressions also permits fast calculation of the output spectral density for higher orders of nonlinearity.